Hair growth at a solid-liquid interface as a protein crystal without cell division. Issue 3 (August 2019) - Chikawa, Jun-ichi; Bandou, Masaichi; Tabuchi, Ken; Tani, Katsuhiko; Saji, Hisashi; Takasaki, Yozo
Abstract: Concentrations of elements in single hair samples were evaluated by X-ray fluorescence by scanning with a narrow beam in the growth direction. Zn binds to the hair protein molecules, and is distributed uniformly from hair tip to root bulb by steady-state growth. To avoid the effect of thickness variation for the bulb, the hair elements were evaluated as the amount per protein molecule using the hair [Zn], resulting in the fault-bounded [S] change typical for a solid–liquid interface; the papilla is in a liquid state and the segregation of elements occurs so as to maintain the amount of shaft element equal to the element inflow into the papilla from the blood, leading to the relationship between hair and blood concentrations. The diffusion boundary layer of S segregation in the bulb gives the diffusion coefficient of D ∼1 × 10 −8 cm 2 /s. The liquid papilla during hair growth solidifies with temperature decrease with the formation of the hair specimen, and the results for solidified papilla are different from the state during growth. It is proposed that the serum protein supplied into dermal papilla changes into precursor keratin molecules, and then into insolvable keratin in the hair matrix cells, i.e., hair makes "protein-melt growth." The pulsed or stepwise variations of [Ca] and [Sr] occur due to the ion channel gating of matrix cells; such variations can never be expected for the cell division growth as deduced from the solidified papilla. The hair growth reflects the status of ion channels and pumping only possible because of the solid–liquid growth interface driven by the gradient in chemical potential nearly perpendicular to the skin surface. Thus, a hair root is a solid–liquid system for hair formation from serum protein.